2012
DOI: 10.2147/lra.s16682
|View full text |Cite
|
Sign up to set email alerts
|

Articaine: a review of its use for local and regional anesthesia

Abstract: Articaine is an intermediate-potency, short-acting amide local anesthetic with a fast metabolism due to an ester group in its structure. It is effective with local infiltration or peripheral nerve block in dentistry, when administered as a spinal, epidural, ocular, or regional nerve block, or when injected intravenously for regional anesthesia. In comparative trials, its clinical effects were not generally significantly different from those of other short-acting local anesthetics like lidocaine, prilocaine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 60 publications
0
63
0
19
Order By: Relevance
“…The canine teeth are innervated by nerve fibers of the most distal portion of the mandibular nerve, which is the mental nerve. For the mental nerve block, a solution of 4% articaine {4-methyl-3-[2-(propylamino)-propionamido]-2-thiophene-carboxylic acid, methyl ester hydrochloride} containing 1:200,000 epinephrine was used (Ultracain D-S Forte), which is currently the most commonly used dental LA in Europe (Cowan, 1977;Snoeck, 2012). Articaine proved to be suitable and safe for procedures requiring a short duration of action in which a fast onset of anesthesia is desired, e.g., dental procedures and ambulatory spinal anesthesia, in normal and in special populations (Snoeck, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The canine teeth are innervated by nerve fibers of the most distal portion of the mandibular nerve, which is the mental nerve. For the mental nerve block, a solution of 4% articaine {4-methyl-3-[2-(propylamino)-propionamido]-2-thiophene-carboxylic acid, methyl ester hydrochloride} containing 1:200,000 epinephrine was used (Ultracain D-S Forte), which is currently the most commonly used dental LA in Europe (Cowan, 1977;Snoeck, 2012). Articaine proved to be suitable and safe for procedures requiring a short duration of action in which a fast onset of anesthesia is desired, e.g., dental procedures and ambulatory spinal anesthesia, in normal and in special populations (Snoeck, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…For the mental nerve block, a solution of 4% articaine {4-methyl-3-[2-(propylamino)-propionamido]-2-thiophene-carboxylic acid, methyl ester hydrochloride} containing 1:200,000 epinephrine was used (Ultracain D-S Forte), which is currently the most commonly used dental LA in Europe (Cowan, 1977;Snoeck, 2012). Articaine proved to be suitable and safe for procedures requiring a short duration of action in which a fast onset of anesthesia is desired, e.g., dental procedures and ambulatory spinal anesthesia, in normal and in special populations (Snoeck, 2012). Similar to other local anesthetics, articaine blocks nociceptive input by reversibly binding to the ␣-subunit of the voltage-gated sodium channels within the inner cavity of the nerve, which results in a state-dependent reduction of sodium influx (Becker and Reed, 2012;Wang et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…VAS Scores greater lipid solubility to articaine as compared to lignocaine. Thereby, it penetrates the nerve membrane more easily and also due to a lower dissociation constant (pKa-7.8) of articaine which is comparable to lignocaine(pKa-7.9) which results in large number of lipophilic free base molecules that are able to diffuse through the nerve sheath thereby lowering the onset time (6,10,11). These characteristics also result in shorter time of onset of hard and soft tissue anaesthesia with articaine (12,13) The present study coincided with the study of Sierra-Rebolledo A et Al (14) who found the difference between the mean subjective onset between 4% articaine with 1:100000 adrenaline and 2% lignocaine with 1:100000 adrenaline to be 19 seconds with articaine having a shorter onset of anesthesia.…”
Section: A Comparative Evaluation Of the Efficacy Of 4% Articaine (1:mentioning
confidence: 99%
“…However, in patients with known deficiency of plasma cholinesterase"s an alternative choice would be appropriate. 6 Articaine has been widely used in dental surgery. Dentists started to use articaine around 1977.In dentistry, articaine has been investigated extensively.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Clinical trials comparing 4% with 2% solutions show no clinical advantage of 4% over a 2% solution Recognizing the importance of providing profound anesthesia for patients undergoing invasive dental procedures, clinicians continually seek to identify an anesthetic solution that provides the highest success rate at an affordable cost. 6 Articaine can diffuse through soft and hard tissues more reliably than other LA so that maxillary buccal infiltration of articaine provides palatal soft tissue anesthesia. 7 The basis for the prevalent use of articaine is due to the belief that it has better diffusion through soft tissue and bone, rapid onset, excellent quality of anesthesia, and lower degree of toxicity than lidocaine.…”
Section: Issn: 2320-5407mentioning
confidence: 99%